The Impact of Learning Model and Classroom Management On Children’s Self-Regulation (An Experimental Research on Group B Kindergarten in Banten, 2017) - Suharto, Sri Wulan; Santoso, Soegeng; Akbar, Ma’ruf (Indonesian Journal of Early Childhood Education Studies, 2018)
This research aimed to find out the impact of learning model and classroom management on the self-regulation of five-to-six-year-old children of Group B Kindergarten in Banten in 2017. It used research method of factorial design 2X2 to explain the difference of children’s self-regulation who got the treatment of learning model and classroom management. The research results: 1) there was an impact of learning model on self-regulation, 2) there was an impact of classroom management on self-regulation, 3) there was an interaction impact between learning model and classroom management on self-regulation, 4) children who were in the center-based classroom management and learned with learning cycle model had higher self-regulation than children who learned with scientific approach model, 5) children who learned with learning cycle model and were in the center-based classroom management had higher self-regulation than children who were in group classroom management. The implication of the research is that combining learning cycle model and center-based classroom management will support the success of the self-regulation development, which is the main provision of the early childhood school readiness.